DESARROLLO DE UN SISTEMA DE GESTIÓN DE ALMACENAMIENTO PARA EMPRESAS PRODUCTORAS DE VINO (CASO-BODEGAS AÑEJAS LTDA) - GABRIEL ESTEBAN GONZÁLEZ ESPITIA; KIMBERLY ALAMET FARFÁN TRUJILLO; EVER ÁNGEL FUENTES ROJAS (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2019)
The storage management system seeks to control logistics processes in the operation as those of purchases, service tothe client, inventory management, storage and transport, to optimize the supply chain; however, several studies use othertools that may be according to the analysis sector. In the case of Bodegas Añejas Ltda. three alternatives were presentedthat allow the development of the storage management system: The supply chain operations reference model that allowsto look for the waste of spaces that affect the conditions of the worker and crossings in the operative flow, whichincreases the times in the activities; the method systematic layout planning that eliminates unnecessary movements in theoperation and finally a simulation in Flexsim where two proposals are proposed to recognize the viability of the changes,where it is possible to increase in 2,108 bottles representing an increase of $ 17,000,000 in monthly sales.